PERSEPSI PETERNAK TENTANG PERANAN PENYULUH DALAM MENINGKATKAN PENGETAHUAN DAN MANAJEMEN PETERNAKAN SAPI DI KELOMPOK TERNAK SAPI SEKAR SARI DESA PANGSAN, KECAMATAN PETANG, BADUNG - Saswita, I M. U.; Suparta, I N.; Suarta, I G. (Jurnal Peternakan Tropika; Volume 1 No. 1 Tahun 2013)
The research, entitled "Perceptions of Farmers Own Role in Improving Knowledge and Extension Livestock Cattle Management" was held at the Cattle Group Sekar Sari, Pangsan Village, the District of Petang, Badung Regency, which runs from April 16, 2012 until June 24, 2012. Livestock group selected by purposive. This activity has 30 respondents. The purpose of this study was to determine the perception of farmers about the role of education in improving the knowledge and management of cattle in the cattle Sekar Sari and analyze the relationship between farmer perceptions of the role of education with the knowledge and management farmers cattle. There variables show the perception of farmers about the education role that analyzed statistically using the nonparametric Spearman Study Correlation Coefficient Test. The research showed that perceptions about the role of education farmers in improving the knowledge and management of cattle in the cattle Sekar Sari has a good category. Perception of farmers about the role of extension workers is positively associated with the level of knowledge is not real farmers, while the farmers perception about the real role of the counselor is positively associated with the management of cattle.
Keywords: Farmers, Role Extension, Knowledge, and Livestock Cattle Management